A photo-dependent capacitance model of GaAs MESFET's - Murty N.V.L.N.; Jit S. (My University, 2025)
A new and simple analytical model for determining the photo-effects on the gate-source and gate-drain capacitances of GaAs MESFET's has been presented for both the linear and saturation regions. A new model for the photovoltage developed across the Schottky junction due to the illumination has been used to investigate the photo-dependent characteristics of the above capacitances. It has been observed that the gate-source and gate-drain capacitances are increased with the increase in the incident illumination level to the device in its linear region of operation whereas in the saturation region, the gate-source capacitance is increased but the gate-drain capacitance is observed to be decreased with the increase in the incident optical intensity level. © 2006 WILEY-VCH Verlag GmbH & Co. KGaA.